Arterial Hypertension as a Risk Comorbidity Associated with COVID-19 Pathology - Alexander Kamyshnyi; Inna Krynytska; Victoriya Matskevych; Mariya Marushchak; Oleh Lushchak (International Journal of Hypertension)
Coronavirus disease 2019 (COVID-19), caused by the novel coronavirus severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), is an ongoing global public health challenge. Current clinical data suggest that, in COVID-19 patients, arterial hypertension (AH) is one of the most common cardiovascular comorbidities; it can worsen outcomes and increase the risk of admission to intensive care unit (ICU). The exact mechanisms through which AH contributes to the poor prognosis in COVID-19 are not yet clear. The putative relationship between AH and COVID-19 may be linked to the role of angiotensin-converting enzyme 2 (ACE2), a key element of the AH pathophysiology. Another mechanism connecting AH and COVID-19 is the dysregulation of the immune system resulting in a cytokine storm, mediated by an imbalanced response of T helper cells subtypes. Therefore, it is essential to optimize blood pressure control in hypertensive patients and monitor them carefully for cardiovascular and other complications for the duration of COVID-19 infection. The question whether AH-linked ACE2 gene polymorphisms increase the risk and/or worsen the course of SARS-CoV-2 infection should also receive further consideration.